Shear Wave Dispersion Imaging for the Characterization of Focal Liver Lesions - A Pilot study - Jesper, Daniel; Fiedler, Steffen; Klett, Daniel; Waldner, Maximilian; Schellhaas, Barbara; Zundler, Sebastian; Neurath, Markus; Pfeifer, Lukas (Ultraschall in der Medizin, 2021)
Purpose Shear wave dispersion imaging is a novel ultrasound-based technique, which analyzes the speed of different shear wave components depending on their frequency. The dispersion of shear wave speed correlates with the viscosity of the liver parenchyma. The aim of this prospective study was to evaluate the use of shear wave dispersion imaging in focal liver lesions in the non-cirrhotic liver. Methods Patients with unclear focal liver lesions in B-mode ultrasound were prospectively assigned to shear wave dispersion imaging (m/s/kHz). Measurements were conducted within the lesion and in the liver parenchyma of the right liver lobe using an intercostal window. Histology and contrast-enhanced ultrasound served as the reference for the characterization of the lesions. Results Out of 46 patients included in this study, 24 had liver metastases and 22 had benign liver lesions. Benign lesions consisted mostly of hemangiomas (n=12) and focal nodular hyperplasia (n=8). Malignant lesions showed significantly lower shear wave dispersion (13.0±2.45 m/s/kHz) compared to benign tumors (15.2±2.74 m/s/kHz, p<0.01). In further subgroup analysis, the difference was significant for hemangiomas (15.32±2.42 m/s/kHz, p=0.04) but not for FNHs (14.98±3.36 m/s/kHz, p=0.38). The dispersion of reference liver parenchyma did not differ significantly between the groups (p=0.54). Conclusion The quantification of viscosity by shear wave dispersion is a new parameter for the characterization of focal liver lesions with higher dispersion values in hemangiomas and lower dispersion values in metastases. However, it cannot differentiate reliably between benign and malignant lesions.
CRIS-Team Scopus Importer:2021-10-29
Keywords: focal liver lesion; shear wave dispersion; shear wave elastography; ultrasound